Nest characteristics and pheromone compounds of Heterotrigona itama Cockerell - Ahmad Jailani, Nur Maisarah (2017)
Stingless bee is known as a potential insect for honey production and recently identified as a novel pollinator for Malaysia. However, the source of stingless bee colonies is entirely depending on feral colony hunting that potentially affects the ecosystem. As the stingless bee industry is growing in Malaysia, understanding their behaviour to support colony splitting, thus preventing feral colony hunting is crucial. To achieve this, specific objectives were outlined; i. To evaluate the nest characteristics of Heterotrigona itama. ii. To determine the correlation between number of queen cells and number of brood layers. iii. To describe the morphology of queen developmental stages. iv. To evaluate the compound in the dufour gland of the egg laying queen of H. itama. Firstly, the colonies were transferred from logs into hives. The colonies from the hives were then split into two. Nest characteristics of the daughter colonies (n=10) were analysed immediately and 12 weeks post-colony splitting based on the height of broods, number of brood’s layer and number of queen cells. Then, the correlation between numbers of queen cell to brood’s layer was performed. The morphology of the queen cell (n=15) was observed based on; i) length x width of the queen cell, ii) the outer layer of the cell, iii) the inner structure of the cell, iv) the comparison of both inner and outer structures, and v) size measurement of the cell. The volatile compounds from egg laying queens’ dufour glands (n=7) were analysed through GC-MS using HP-5MS column. Nest characteristics of daughter colonies immediately after colony splitting showed that the height of broods was 16.20 ± 4.29, followed by the number of broods’ layer of 8.9 ± 26.7 and 5.2 ± 15.6 virgin queen egg. After 12 weeks, the height of broods became 16.41 ± 4.45 with 12.1 ± 36.3 broods’ layer and 6.4 ± 19.2 virgin queen egg. For all the 10 colonies, the difference between two layers of broods showed a fixed value of 1.5 cm before and after 12 weeks observation. The numbers of queen cell and broods layer within the 12 weeks were significantly different where F = 9.471, P< 0.0001 and F = 7.646, P< 0.0001, respectively. However, the correlation between the two characters was significantly low (r = 0.421). Morphological analysis showed nine fully formed queens while six of them were still at development stage. Finally, from GC-MS analysis, results demonstrated that the area percentage of volatile compounds octadecane, heneicosane octacosane and pentacosane was more than 3% with octadecane and pentacosane, and heneicosane and pentacosane being statistically significant to one another. As a conclusion, nest characteristics and queen’s morphology of H. itama have been successfully described with the compounds presented in the dufour gland of the egg laying queen that have been evaluated. Data from this study may provide a better understanding for the establishment of stingless bee colony splitting technique.